Evaluating the reactivity controlled compression ignition operating range limits in a high-compression ratio medium-duty diesel engine fueled with biodiesel and ethanol. (February 2017) - Benajes, Jesús; García, Antonio; Monsalve-Serrano, Javier; Balloul, Iyad; Pradel, Gérard
This work investigates the load limits of reactivity controlled compression ignition combustion, a dual-fuel concept which combines port fuel injection of low-reactivity fuels with direct injection of diesel fuel, in a medium-duty diesel engine. The experiments were conducted in a single-cylinder diesel engine derived from the multi-cylinder production engine. In this sense, the stock turbocharger and exhaust gas recirculation systems were replaced by an external compressor and dedicated low-pressure exhaust gas recirculation loop, respectively. Additionally, a port fuel injector was installed in the intake manifold to allow gasoline injection. First, this article presents some results highlighting the effect of the exhaust gas recirculation rate, gasoline fraction, diesel start of injection, diesel injection strategy and intake temperature on the emissions, performance and combustion development in a representative operating condition: 1200 r/min and 6.5 bar indicated mean effective pressure (25% load). Later, with the aim of showing the reactivity controlled compression ignition potential, the best results in terms of performance and emissions at 25% load are compared against the multi-cylinder diesel engine from 950 to 2200 r/min. Reactivity controlled compression ignition engine tests were developed taking into account limitations in nitrogen oxides (NOx) and soot emissions, in-cylinder pressure and maximum pressure rise rate. Finally, keeping the same constraints for testing, the load limits of reactivity controlled compression ignition concept are evaluated for all the engine speeds. Results suggest that reactivity controlled compression ignition allows fulfilling EURO VI limits for NOx and soot emissions without using selective catalytic reduction and diesel particulate filter aftertreatment systems at 25% load at all the engines speeds, providing better indicated efficiency than conventional diesel operation in most operating points. In addition, the maximum engine load that ensured the aforementioned constraints was around 35% for all the engine speeds, with a maximum indicated mean effective pressure of 8.8 bar at 2200 r/min. In this case, a strong reduction in carbon monoxide (CO) and unburned hydrocarbon (HC) emissions compared to the cases of 25% load was achieved at all the engine speeds.